DNA Barcoding Analysis Kitolod (Hippobroma longiflora) from Riau Based on matk Gene - Herman, Herman; Sari, Mayang; Multivasari, Nella; Roslim, Dewi Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The kitolod plant (Hippobroma longiflora) is a traditional medicinal plant originating from the Campanulaceae family. DNA barcoding is a technique for identifying an organism using short nucleotide sequences known as DNA barcoding. One of the DNA barcodes in plants is matK. This research aims to analyze DNA barcode sequence in the matK region of the kitolod plant using the DNA barcode. Samples were taken from the area of Tarai Bangun Village, Kampar Regency, Riau Province, Indonesia as many as two different individuals. The research stages carried out are sampling, followed by DNA isolation using the Geneaid Mini Plant kit, PCR follow thermo scientific instructions, gel agarose electrophoresis, sequencing, and data analysis using the bioinformatics program, namely BioEdit, BLASTn, and MEGA 6.0. The matK sequence of the kitolod plant obtained was 841 bp. The result showed that no identity value was found to reached 100%. The highest identity value (99.88%) was found in H. longiflora NC_035361.1. 34 nucleotide variations were found with one critical nucleotide for H. longiflora from Riau and six critical nucleotides for the H. longiflora. The matK DNA sequence from Kitolod Riau in this study is the first sequence reported in database GenBank.